Mauro Orbini in the Croatian and Serbian Cultural Context - Roić, Sanja (2013)
Orbini's book Il Regno degli Slavi was created as a result of South Slav-Italian interferences on linguistic, culturological and historical level. It also confirms that a comprehensive view of the concept of Slavism was possible at the time from a distance, from the context of alterity, in this case from the nearest „other“, neighbouring Italian culture which enabled an insight into European historiography, which is yet another confirmation that intellectuals by origin from Dalmatia acquired their European cultural horizon via Italian culture.
Projekt MZOS
ENG